Interprofessional approaches in research planning training: Multidisciplinary perspective in oral and dental health - BAYRAM, FERİT; SABUNCULAR, GÜLEREN; ÇELİK, ZEHRA MARGOT; İSLAMOĞLU, AYŞE HÜMEYRA; AKTAÇ, ŞULE (My University, 2023)
Objectives: This study evaluates the effectiveness of an interdisciplinary educational intervention in improving the perceptions of interdisciplinary education, research competency, and research anxiety among postgraduate students in various health disciplines. Materials and Methods: This prospective cohort study was conducted at Marmara University during November 2023. A two-day training program, “Multidisciplinary Approach to Oral and Dental Health” was conducted, involving educators and postgraduate students from dentistry, speech and language therapy, nutrition and dietetics. The program consisted of four modules, combining didactic training and workshops. Data were collected pre-post-intervention using validated scales: Interdisciplinary Education Perception Scale (IEPS), Research Competency Scale (RCS), and Research Anxiety Scale (RAS). Scores were analyzed using a t-test for pre-test and post-test calculations. In the findings, a p-value of <0.05 was considered statistically significant. Results: Initially, 30 participants were registered for the study, but the final analysis was conducted on 26 participants. The statistical analysis indicated significant improvements in the postintervention scores for both the IEPS and the RCS. The average score for IEPS increased from 86.65 before the intervention to 91.04 after (p=.028), and for RCS, it rose from 25.92 to 28.08 (p=.010). However, RAS showed no significant change, with scores averaging 30.85 before and 30.65 after the intervention (p=.710). Conclusions: The intervention effectively enhanced interdisciplinary education perception and research competency among participants, emphasizing the potential of short-term, structured multidisciplinary programs in postgraduate dental education.
Keywords: Diş Hekimliği; Beslenme ve Dietetik; Sağlık Bilimleri; Dentistry; Nutrition and Dietetics; Health Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Tarım Bilimleri; Klinik Tıp; BESLENME VE DİYETETİK; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); AGRICULTURAL SCIENCES; CLINICAL MEDICINE; NUTRITION & DIETETICS; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Beslenme ve Diyetetik; Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Interprofessional relations; dentistry; speech therapy; dietetics; research